1988
DOI: 10.1002/aic.690340202
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion‐free solvent extraction with microporous hollow‐fiber modules

Abstract: Extensive studies on dispersion-free solvent extraction have been carried out using modules made with either hydrophobic or hydrophilic microporous hollow-fiber membranes. Membrane and boundary layer resistances have been characterized for both kinds of hollow fiber using solvent extraction systems with a wide variation of distribution coefficients and interfacial tensions. It has been found that the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
232
1
9

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(251 citation statements)
references
References 17 publications
9
232
1
9
Order By: Relevance
“…This may be due to relatively minor changes in the fluid dynamics in the shell side (Re f decreased gradually from 1100 to 674). It should be noticed that a similarly complex relationship between the packing density and module performance were observed in many studies involving shell-side flow distribution when using gas-liquid hollow fiber membrane contactors [27,28,30,32,45].…”
Section: Fiber Packing Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to relatively minor changes in the fluid dynamics in the shell side (Re f decreased gradually from 1100 to 674). It should be noticed that a similarly complex relationship between the packing density and module performance were observed in many studies involving shell-side flow distribution when using gas-liquid hollow fiber membrane contactors [27,28,30,32,45].…”
Section: Fiber Packing Densitymentioning
confidence: 99%
“…6 However, there are limited reports available on improving fluid dynamics and designing hollow fiber modules for MD applications in the open literature [22][23][24][25]. Some relevant studies have focused on the effect of packing density, flow maldistribution and hydrodynamic behavior in the shell side of hollow fiber modules, based on studies of various gas-liquid/ liquid-liquid contactors [26][27][28][29][30][31]. It is widely accepted that non-ideal flow distribution leads to less active membrane area and insufficient mass transfer, and thus poor module performance.…”
Section: Introductionmentioning
confidence: 99%
“…As a comparison, the mean pore tortuosity of flat and hollow fiber polyproplylene MF membranes ranges between 1.9 and 2.8 [16,17].…”
Section: Pore Structure Of Spg Membranesmentioning
confidence: 99%
“…Nevertheless, many prior studies on general hollow fiber module work have shown that non-ideal flow distribution in a module will lead to less active membrane area, insufficient mixing and local loss of driving force, and hence low heat-or mass-transfer efficiencies [5][6][7][8][9][10][11][12].Studies on hydrodynamic improvement in MD hollow fiber modules are sparse in the open literature, mainly due to fabrication and modeling complications [2,[13][14][15][16].Enhancing strategies such as flow alteration aids or modifying fiber geometries to create secondary flows or eddies (such as novel fiber configurations or turbulence promoters, e.g. spacers or baffles) have been proposed for improving MD module performance [15][16][17].…”
Section: Introductionmentioning
confidence: 99%